Comportamiento agronómico del cultivo de arroz (oryza sativa) en respuesta a la fertilización con bioestimulantes orgánicos bajo condiciones de secano en la zona de Mocache. - Montese Arriaga, Rubén Darío (2016)
This research was conducted to evaluate the effect of the application of organic bio-stimulants in rice (Oryza sativa) under rainfed conditions in the area Mocache. The culture was established on grounds of the estate of Mr. Pedro Montese, located in the canton Mocache province of Los Rios. The trial was conducted under a design randomized complete block factorial arrangement 3x3 + 2 in 3 replications. As the organic bioestimulantes factor A and factor B the application doses, whose interactions were compared with a farmer witness and a chemical control, and the statistical difference it was established by Duncan test at 95% probability. The main results appreciated that when applied biol higher plants were obtained exceeding 0.5 cm and 4.0 cm to super broth four manure tea in order, 1.1 and 12.2 tillers per square meter rather than the latter also did not differ in the number of panicles per square meter, whose values ranged between 250.2 and 257.3, with the average biol which recorded higher. By using biol occurred 5.4 and 7.3 grains per panicle than manure tea and broth super four. The yield obtained by the application of biological differed in only 16.1 Kg / ha of super broth four being greater the difference with manure tea with 447.6 Kg / ha. The dose of 100 l / ha produced plant exceeded 5.4 and 9.0 cm to those obtained with doses of 50 and 25 l / ha, respectively; 23.9 and 33.1 also produced more tillers per square meter, 13.2 and 18.1 panicles per square meter 11.5 and 13.6 grains per panicle, and 473.6 and 809.8 kg / ha more than with 50 and 25 l / ha, respectively. A treatment level, applying 100 l / ha biol plants exceeded only 2.8 and 3.2 cm to chemical control and the application of super broth presented in four doses of 100 l / ha. The three bioestimulantes in doses of 100 l / ha each were not significantly different chemical produced 477.3 witness tillers per square meter. With biol in doses of 100 l / ha was obtained 7.4 panicles per square meter more than the chemical witness. By applying biol in doses of 100 l / ha 9.4 and 10.5 grains per panicle than super broth with four doses of 100 l / ha and chemical control was obtained. The chemical control barely exceeded 96.6 kg / ha to biol in doses of 100 l / ha and 158.8 kg / ha super broth four at the same dose. The greatest economic benefit was obtained with the chemical control with $ 896.16, with a yield of 114%.